Um estudo sobre a cultura chinesa e a condução das empresas brasileiras instaladas na China - Melo, Suzana Assis Bandeira de (2013)
In the current scenario that presents China as Brazil s largest trading partner, there has been a significant growth of Brazilian companies that trade with the Asian country. Nonetheless, it is also observed that only a few of these companies have established presence in Chinese territory. According to recent research, this physical and cultural distance is pointed as the main barrier to the entry and further access to China. This dissertation seeks to explore the cultural differences that influence the deployment and administration of businesses in China and has identified four traits playing a crucial role: language/communication, hierarchy, "Face" (mianzi) and guanxi (relationship network).These elements were described based on literature and field research with four Brazilian companies in China. The case studies explored qualitative and descriptive aspects, featuring the testimony of seven Brazilian leaders, responsible for the management of these companies in China. It was concluded that learning about Chinese culture could be basic premise to reach a well-established and steady business in China, although it does not guarantee a successful adaptation. Moreover, managers on the front line have the greatest responsibility in managing and carrying out the adaptation, which implies that, partially, the idiosyncratic characteristics of these leaders can be a major factor to determine the adaptation of the franchise and overall success of the venture. The issue of diversity and cultural differences make up a spectrum of variables that can affect the internationalization of enterprises to China. Thus, taking into account cultural diversity becomes an essential part of the business strategy and one that can represent a great competitive advantage. It is expected that by delivering greater knowledge about China and its culture, the results of this thesis can contribute to reduce the cultural distance between the Asian country and Brazilian companies